Characterization of Relaxant Responses to Natriuretic Peptides in the Human Microcirculation In Vitro and In Vivo. (August 2016) - Edvinsson, Marie‐Louise; Ahnstedt, Hilda; Edvinsson, Lars; Andersson, Sven E.
Abstract: Objective: We characterized the vasodilatory effects of ANP, BNP, and CNP in human subcutaneous arterioles in vitro and the cutaneous microcirculation in vivo . Methods: The in vitro experiments were performed using wire myography and the responses were characterized by the use of inhibitors for nitric oxide (L‐NAME), prostaglandin synthesis (indomethacin), or the endothelium‐derived hyperpolarization factor. In vivo, the vasorelaxant effect of iontophoretically administrated BNP or CNP was measured with a noninvasive laser Doppler technique. Involvement of nitric oxide or prostaglandins was assessed by L‐NAME or indomethacin given by iontophoresis. Results: In vitro all three peptides showed significant vasodilatation with the efficacy order: CNP > BNP = ANP. The BNP‐induced vasodilatation, but not that of ANP or CNP, was significantly reduced by pretreatment with indomethacin or L‐NAME. In vivo administration of BNP induced a marked vasodilatory response that was attenuated by local pretreatment of L‐NAME. Indomethacin by itself resulted in increased cutaneous perfusion. Conclusions: NPs are potent vasodilators in the human subcutaneous circulation. The response to BNP differs from that of the other peptides as it seems dependent on cyclooxygenase products and nitric oxide.